Efficacy and safety of acupuncture as an adjuvant therapy for osteoporosis: a systematic review and meta-analysis of randomized controlled trials - Teng, Zixin; Zhu, Jingwei; Li, Kuiwu; Tong, Tingting; Li, Wei; Chu, Haoran; Sun, Peiyang (Frontiers in Endocrinology, 2025)
ObjectiveTo systematically evaluate the efficacy and safety of acupuncture as an adjuvant therapy for osteoporosis (OP) through a comprehensive synthesis of recent randomized controlled trial (RCT) evidence.MethodsA systematic literature search was conducted across PubMed, Web of Science, CNKI, and Wanfang databases (2014 – 2024) to identify RCTs investigating acupuncture combined with conventional therapy for OP. Study quality was appraised using the Cochrane Risk of Bias tool, and meta-analyses were performed using RevMan 5.4 and Stata 15.0, with subgroup analyses stratified by intervention type, population characteristics, and treatment duration.Results28 RCTs (n=2,758) were included. Meta-analysis revealed acupuncture significantly enhanced bone mineral density (BMD) versus controls: total (SMD = 0.47, p = 0.03), femoral neck (MD = 0.05, p = 0.01), lumbar spine (SMD = 0.40, p < 0.001), Ward’s triangle (MD = 0.07, p = 0.02), and hip (SMD = 0.55, p < 0.001), with particularly marked improvements in the postmenopausal osteoporosis subgroup. Acupuncture demonstrated significant improvements in treatment efficacy, biochemical markers, pain scores, and symptom assessments, while reducing adverse events. Warm needle moxibustion outperformed controls in femoral neck (MD = 0.07, p = 0.002) and hip BMD (SMD = 0.87, p < 0.001), while electroacupuncture significantly elevated serum calcium (MD = 0.18, p = 0.02). Short-term interventions (≤ 3 months) demonstrated optimal efficacy.ConclusionAcupuncture demonstrates efficacy and safety as an OP adjuvant therapy. Current evidence is limited by regional bias and methodological heterogeneity. Multicenter, large-sample RCTs are needed to standardize protocols and validate long-term therapeutic efficacy.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024499354.